A Representative National Police Commission in Realizing the Professionalism of the Indonesian National Police - Sri Widayatai; Diana Haiti; Rahmida Erliyani; Anang Shophan Tornado (Dinasti Research, 2026)
The National Police of the Republic of Indonesia (Polri) has a vital constitutional mandate, but the integration of large authorities without strong external oversight creates a risk of abuse of authority and a decline in public trust. This study aims to analyze the nature of the position and juridical limitations of the National Police Commission (Kompolnas) and formulate the urgency of reconstructing the institution so that it becomes representative in realizing the professionalism of the National Police. Using normative legal research methods with a qualitative approach, this study dissects the position of the National Police Commission as a state auxiliary organ through the theory of representative bureaucracy. The findings of the study show that the National Police Commission experiences normative ambiguity and an